The Effects of Audience Response Systems on Active Learning - Mantikayan, Jonathan Mamangkiang; Ayu, Media Anugerah; Mantoro, Teddy; Mohammed, Hasni (2012)
Research literature shows that isolation and lack of interaction and engagement exist in traditional classes. Audience Response Systems (ARS), which have been identified as a potential, innovative solution, to aid in fixing disconnection associated with traditional education practices. The aim of this paper is to investigate the effects of audience response systems on student active learning in secondary education. The sample learning institution in this research is Adni International Islamic School. This study used survey and observation method to determine the effect of audience response systems on active learning in computer studies class at Adni International Islamic School. Based on the pilot study’s findings, continued use of audience response systems is recommended. ARS can trigger student active learning. ARS give teachers a means of presenting information and gauging comprehension while engaging students. Students learn using various learning styles and audience response systems give teachers another opportunity to meet those varied styles of learning. Changes in delivery of instruction are needed to meet all learning styles of children today. Leaders in education should embrace technological changes and incorporate them into instruction. Audience response systems may provide that change in instructional practices.